Analisis sistem dan prosedur pemungutan pajak reklame sebagai upaya peningkatan Pendapatan Asli Daerah di Badan Pendapatan Daerah Kota Manado - Karouw, Seren Friska; Sabijono, Harijanto; Walandouw, Stanley Kho (Yayasan Widyantara Nawasena Raharja, 2024)
Of the various types of taxes collected by the Manado City Government, advertisement tax is one type of tax that can develop its role in increasing local revenue. This research was conducted with the aim of finding out the system and procedure for collecting advertisement tax as an effort to increase PAD. The methode used is descriptive qualitative method. The research results show that the advertisement tax collection system uses an official assessment system based on Law Number 28 of 2009. The procedure for collecting advertisement tax has been carried out in accordance with Manado Mayor Regulation Number 57 of 2013 concerning Technical Guidelines for Implementation of Advertising Tax Collection. However, it can be seen from the payment procedure that there are still taxpayers who do not carry out their obligations in paying advertisement tax and do not register their advertisement tax objects. It is better for the Manado City Government, in this case the Manado City Regional Revenue Agency, to socialize again to taxpayers about the techniques of advertisement tax collection and prosecute those who break the rules.